TWENTY-FIRST CENTURY SABAR DRUMS: INNOVATIONS IN ORGANOLOGY AND PERFORMANCE PRACTICES IN SENEGAL AND THE DIASPORA - Tang, Patricia (International Library of African Music, 2019)
This article contributes to the substantial body of publications on South African jazz with information on jazz performance and performers in New Brighton, a township adjacent to Port Elizabeth noted for its vibrant jazz scene and outstanding jazz musicians. The article covers several decades from the heyday of swing bands in the 1940s—50s through the 1960s—70s when New Brighton's premier jazz combo, the Soul Jazzmen, were at the height of their artistry. The role of swing bands in New Brighton and surrounding communities as the training ground for members of the Soul Jazzmen and other local musicians of note is discussed, as well as how the Soul Jazzmen in turn were tutors for musicians of the next generation who became widely recognized artists, composers and arrangers. This is followed by a focus on the Soul Jazzmen and compositions by its members that protested against the apartheid regime in the 1960s—70s. The article is informed by historic photographs, newspaper clippings and information from oral history interviews that richly document how jazz was performed in service of the anti-apartheid struggle in New Brighton.
Keywords: Drum; Djembe; Ecomusicology; Musical instruments; Drum music; Climate changes; Sabar (Instrument); Sanegal; African Music; Drum (Instrument)